PROFIL BERPIKIR REFLEKTIF SISWA SD DALAM PEMECAHAN MASALAH PECAHAN BERDASARKAN KEMAMPUAN MATEMATIKA - Hery Suharna; Agung Lukito Nusantara; I Ketut Budayasa (EDUKASI, 2016)
The research reveals a profile of reflective thinking of elementary school students in problem solving fractions based on his mathematical abilities. The instruments used in data collection is Test Problem Solving (TPM), interview. Selection of research subjects in a way given test is based on the ability of mathematics, namely mathematical skills of high, medium and low and further categorized and taken at least 2 people to serve as subjects. The research objective is: describe the profile of reflective thinking that math skills of elementary school students High, medium, and low. Based on the results of the study found reflective thinking profile and high ability students were as follows: (a) the step to understand the problems students have information/knowledge or data that is used to respond, comes from inside (internal) and can explain what has been done; (B) the planned step problem solving students have information/knowledge or data that is used to respond, comes from inside (internal) and can explain what has been done; (C) on measures to implement the plan in terms of information/knowledge or data used by students to respond, comes from inside (internal), could explain what has been done, realized the error and fix it, and communicate ideas with a symbol or image, and (d) the checking step back, namely information/knowledge or data that is used by students to respond, comes from inside (internal) and can explain what has been done. Profile of reflective thinking ability students lowly mathematics, namely: (a) at the stage of understanding the problem, students can determine known and asked in the problem, but the students' difficulties to explain the identification of the facts that have been done, the students explained the understanding vocabulary, and feel of existing data the matter is enough; (B) at the stage of implementing the plan, the students explained, organize and represent data on the issue, describes how to select the operation in solving a problem though students are not sure, and students' difficulty in explaining what he had done; (C) at the stage of implementing the plan, the student has information on calculation skills although the answer is not correct. Students difficulty in explaining about the skills calculations have been done, trying to communicate their ideas in the form of symbols or images, even if students rather difficult to describe, and realized there was an error when using a calculation skills and improve it; (D) at the stage of check, students' difficulties in explaining whether obtained estimates it approached, it makes senseKeywords: reflective thinking, problem solving, fractions, and math skills.